Developing Peripheral Learning Material to Improve Students’ Vocabulary for The Fifth Grade of Elementary School - Saputra, W. (Universitas Pendidikan Ganesha, 2019)
This study aimed at developing peripheral learning material in an attempt to improve fifth grade students’ vocabulary. This study used ADDIE model proposed by McGriff to develop the product. The stages used were (1) Analyze, (2) Design, (3) Develop, (4) Implement, and (5) Evaluation. Based on the result of need analysis it can be concluded that the peripheral learning material produced was in the form of poster that contained word, picture and simple sentence by concerning the criteria of the good material and poster. The interview guide and questionnaire were used in this stage as the instruments. After analyzing the needs, the product was design by making the blueprint, draft, illustration as well as inserting the word and sentences. The product was revised and developed in the development stage. Furthermore, the product was implemented in limited trial by attaching the poster around the class, conducting the first observation, changing the poster, and conducting the second observation. The response of the students and the teacher were gained by using the questionnaire and the interview. In order to check the quality of the product, the expert judgement sheet was used as the instrument. From both of expert judges it can be categorized that the product was excellent product.